Gel against denture stomatitis: clinical report - Tay, Lidia Yileng; Santos, Fabio André dos; Jorge, Janaina Habib [UNESP] (Wiley, 2015)
The objective of this study is to report the clinical use of 2% Uncaria tomentosa gel against denture stomatitis (DS) as an alternative treatment. The patient was a 65-year-old, denture-wearing woman. At the clinical examination, her palate showed hyperplasic and erythematous mucosa indicating DS type II. DS is a chronic oral disease that affects denture wearers. It occurs as an inflammatory reaction in denture-wearing patients under maxillary prostheses. Candida albicans has been reported as the principal etiological agent. An alternative treatment, the topical application of a gel of 2% U. tomentosa three times a day for 1 week was given to the patient. After 1 week of this treatment, she had significantly reduced signs of the disease. Despite the existence of a great number of antifungal agents, treatment failure is observed frequently. Phytotherapy is becoming more popular worldwide. Currently, the most promising medicinal Amazonian herb is U. tomentosa (Willd.) DC., known as Cat's Claw. Studies of the chemical and pharmacological properties of this medicinal plant have allowed researchers to develop indications for its use. This report demonstrates the effectiveness of U. tomentosa against DS.
Keywords: Cytotoxicity; Medicinal plant